STUDI KUALITAS REPAIR WELDING MENGGUNAKAN METODE OXY-ACETYLENE DENGAN PWHT PADA CAST WHEEL ALUMINIUM - Wilopo, Irman Azis (Jurnal Nosel, 2014)
The purposes of this research are: (1) To determine the chemical composition and aluminum alloy standard codification of cast wheel aluminum. (2) To determine the microstructure before and after welding with oxy - acetylene welding method with PWHT on the cast aluminum wheel. (3) To determine the level of hardness and level of impact strength before and after welding with oxy - acetylene welding method with PWHT on the cast wheel aluminum. The research was conducted in the laboratory INLASTEK Surakarta. The Object in this research used are aluminium cast wheels. Techniques of data analysis in this research using descriptive data analysis that is directly observed experimental results and then analyzed and summing up the results of the research. As an input parameter in analyzing the data include:the testing of chemical composition, microstructure, hardness and impact. From the research, we can conclude that the chemical composition on aluminium cast wheel including Aluminium Silicon alloy, because the element Si alloy is the largest with 4.61% Si. Microstructure on base metal granules the spread equally on the surface of Al. Specimen hardness value of raw material is higher than oxy-acetylene welding specimens. The average value of raw material hardness results 42.69 BHN while the average value of oxy-acetylene welding results 34.34 BHN. Average hardness oxy-acetylene welding specimens in the HAZ area 31.81 BHN. The average value of raw material impact results 0,092 J/mm² while the average value of oxy-acetylene welding results 0,078 J/mm². Post-weld heat treatment (PWHT) was effect on the mechanical properties and microstructural that characterized by nearly changes in the microstructure between the weld region, HAZ , and base material after PWHT process .